Alexander Fleming: a second look - Danielle Gerberi (Journal of the Medical Library Association, 2024)
In 1928, Alexander Fleming (1881-1955) identified penicillin, the world's first antibiotic. It was a chance discovery that could have easily been missed had Fleming not taken a second look at a contaminated Petri dish. The discovery of penicillin marked a profound turning point in history as it was the first time deadly infections such as bacterial pneumonia, sepsis, diphtheria, meningitis, and puerperal fever after childbirth could be cured, and it paved the way for the development of additional antibiotics. The Alexander Fleming Laboratory Museum, one of several London Museums of Health and Medicine, is a reconstruction of Fleming’s laboratory in its original location at St. Mary’s Hospital. As if stepping back in time, visitors gain a glimpse into the man, his bacteriology work, and the events surrounding this important finding. For those unable to travel to London, this article provides a brief narrative of the fascinating story.